Revisiting the virtues of veto point: political corruption in post-Soeharto Indonesia. Issue 2 (2nd April 2020) - Lele, Gabriel
ABSTRACT: This article expects to extend existing researches on the effect of political institutions on political corruption. Examining the case of post-Soeharto Indonesia, it argues that political corruption has become more rampant because of structural opportunities which incentivize corrupt practices. Employing veto player theory, this article illustrates how the conventional wisdom of installing more veto players has worked counterproductively to increase rather than to constrain political corruption. This is explained by the nature of the legislative process, which requires all players to agree before any legislative proposal can be enacted. Instead of ensuring checks and balances, the dispersion of more institutional veto players has been used as a political instrument to frustrate the executive. Bribery is used as a remedy for speeding up budget-making processes and getting priority policies approved. This article concludes that the veto player system needs to consider the nature of legislative processes in a specific context.